Systems Thinking Analyses for Health Policy and Systems Development A Malaysian Case Study - Martins, Jo. M.; Pathmanathan, Indra; Tan, David T.; Cheng Lim, Shiang; Allotey, Pascale (Social Sciences, 2021)
Using systems-thinking tools for the first time to understand an entire national health system, this book will be of immense value to academics, students and policymakers. The case study of Malaysia shows that a people-centred health system can be constructed successfully within existing and evolving resource constraints and priorities.?